PENGEMBANGAN KREATIVITAS SISWA MELALUI POTENSI BUDAYA LOKAL DALAM PEMBELAJARAN SENI TARI - Leny Susanti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Creativity is the ability of a person to give birth to something new, both in the form of ideas and real works that are relatively different from what has been there before. The process of student creativity usually begins with an example of the teacher's creative process. Being a creative, professional and fun teacher is required to have the ability to develop approaches and choose effective learning methods. Art learning is a business process carried out by a person to obtain a change in attitudes and behavior as a result of artistic experience and interacting with environmental culture to achieve certain goals. By Developing Student Creativity Through the Potential of Local Culture in Learning Dance Arts Tanjung Raja High School 2 is expected to get to know more about the culture around it and be able to increase creativity in art education.